Equity in temporary street closures: The case of London's Covid-19 'School Streets' schemes. (September 2022) - Thomas, Asa; Furlong, Jamie; Aldred, Rachel
Highlights: Mixed picture for socio-economic and demographic equity, in some cases equal but not equitable. School Streets are less likely at schools in areas with worst air quality and high car dominance. There are significant differences in provision between London's borough authorities. Policies for hard-to-treat schools are needed to improve air quality inequities. Abstract: School Streets are a street space reallocation scheme that has proliferated since the beginning of the Covid-19 pandemic in the UK, reducing motor traffic on streets outside many schools. Utilising a minimum-standards approach to equity, this paper examines the distribution of School Streets closures across social and environmental indicators of equity, and spatially across London's administrative geography. Using a multi-level regression analysis, we show that although School Streets have been equally distributed across several socio-demographic indicators, they are less likely to benefit schools in car-dominated areas of poor air quality, and their spatial distribution is highly unequal. This study presents an example of using environmental and spatial variables alongside more typical sociodemographic indicators in measuring the equity of school travel provision. For policymakers, the findings signal the need to implement complementary policies that can benefit schools with worse air quality, and to accelerate School Street implementation in slower districts.